γ -valerolactone as a green solvent for the delignification of sugarcane bagasse - González, Roxana Giselle (2022)
Biorefineries based on lignocellulosic biomass have become relevant for reducing emissions and replacing fossil resources. Sugar platform biorefineries employ carbohydrates sugars derived from cellulose and hemicelluloses. Carbohydrates and lignin form a complex structure, so they must be separated by delignification using chemicals and specific experimental conditions. The application of green solvents is a strategy that will allow processes optimization with minimal environmental impacts. γ-valerolactone is a promising candidate because it is a bio-based organic solvent with low toxicity, high water solubility, low melting point, high boiling point, and lower recycling costs. This study evaluated γ-valerolactone as an organosolv treatment for the delignification of sugarcane bagasse. It could be a green option to include in a lignocellulosic biorefinery.The delignification conditions of sugarcane bagasse in a mixture of γ-valerolactone and water were analyzed using a Draper-Lin central composite experimental design evaluating four factors: temperature, time, γ-valerolactone concentration, and sulfuric acid load. This last one was used as a catalyst in concentrations lower than 0.01M. The liquor/solid ratio was 10:1. Pulp yield, ISO brightness, total structural carbohydrates, lignin content, delignification percentage, intrinsic viscosity (ƞ), and crystallinity index were evaluated as response variables. Results showed that high levels of the variables produce lower yields, lignin content, and ƞ (minimums values of 40.5 wt%, 2.32 % on dry basis (odb), and 140 mL/g,) in addition to higher brightness, delignification, and crystallinity index (maximums values of 58.1% 96.2%odb, and 80.0%). The ƞ correlated with pulp yield (r=0.95) and crystallinity index with total lignin content (r=-0.98). The optimization for delignification, ƞ, and glucans using the Desirability function indicated that the treatment at 152 ºC, for 60 min, 43 wt% of γ-valerolactone, and 0.0083 M of sulfuric acid produce theoretical maximums of 89%odb delignification, ƞ=791 mL/g, and 84%odb of glucans in the pulp. These results prove that acid, even at low concentrations, is needed for delignification, and its effect is significant for all the response variables. However, there was an appreciable amount of shives, possibly because of the acid media.